Non-high-density to high-density lipoprotein cholesterol ratio and its association with infertility in U.S. women: a cross-sectional study - Zhang, Yajie; Lu, Cong; Li, Lili; Li, Hongyu (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the relationship between Non-High-Density Lipoprotein Cholesterol to High-Density Lipoprotein Cholesterol Ratio (NHHR) and infertility in US female adults aged 20 to 45.MethodsOur research team utilized data from the 2013–2018 National Health and Nutrition Examination Survey (NHANES) to conduct a cross-sectional study. Multivariable logistic regression was conducted to examine the association between NHHR and infertility, with trend tests providing additional insight into this relationship. Further, smoothed curve fitting was applied for a more detailed exploration. To ensure the robustness of our results, we conducted subgroup and sensitivity analyses.ResultsBetween 2013 and 2018, our study included 2,947 participants, with 342(11.6%) self-reported infertility. A positive association was found between NHHR and infertility (OR=1.17,95%CI:1.07-1.27). Compared with the first trimester, the third trimester of NHHR was associated with an OR of 1.79(95% CI: 1.31–2.44) in model 3. The results of subgroup analyses revealed that the association between NHHR and infertility was nearly consistent.ConclusionNHHR demonstrated a positive correlation with infertility among U.S. female adults. Further investigation is needed to explore their association better and the underlying mechanisms.